Design of Slotted and Slotless AFPM Synchronous Generators and their Performance Comparison Analysis by using FEA Method - Saint Saint Soe; Yan Aung Oo (Institute of Advanced Engineering and Science, 2015)
Axial-flux permanent magnet machines are popular and widely used for many applications due to their attractive features such as light weight, low noise, high torque, robust and higher efficiency due to lack of field excitation. The main essence of this paper is to perform slotted and slotless axial-flux permanent magnet synchronous generator design based on theoretical sizing equations and then finite element analysis is reinforcement in order to get a more reliable and accuracy machine design. A comparative study of machine design and performances over the same rating but different configurations i.e., slotted and slotless are also discussed. And then, finite-element method (FEM) software was made for the slotted stator and slotless stator (AFPMSG) in order to compare their magnetic flux density and efficiency. The AFPMSG topology considered in this paper is a three-phase double-rotor single-stator topology with 16 pole-pairs, 2kW rated power and 188 rpm rated speed.